Phonetic accommodation in interaction with a virtual language learning tutor: A Wizard-of-Oz study. (May 2021) - Gessinger, Iona; Möbius, Bernd; Le Maguer, Sébastien; Raveh, Eran; Steiner, Ingmar
Highlights: We investigate phonetic accommodation of German native speakers in interaction with the simulated spoken dialog system Mirabella. Two versions of Mirabella are compared: one uses pre-recorded speech and the other synthesized speech. In both conditions, speakers converge to Mirabella regarding the intonation of wh-questions and one of two investigated allophonic contrasts. Abstract: We present a Wizard-of-Oz experiment examining phonetic accommodation of human interlocutors in the context of human-computer interaction. Forty-two native speakers of German engaged in dynamic spoken interaction with a simulated virtual tutor for learning the German language called Mirabella . Mirabella was controlled by the experimenter and used either natural or hidden Markov model-based synthetic speech to communicate with the participants. In the course of four tasks, the participants' accommodating behavior with respect to wh-question realization and allophonic variation in German was tested. The participants converged to Mirabella with respect to modified wh-question intonation, i.e., rising F0 contour and nuclear pitch accent on the interrogative pronoun, and the allophonic contrast [ɪç] vs. [ɪk] occurring in the word ending 〈 -ig 〉 . They did not accommodate to the allophonic contrast [ɛː] vs. [eː] as a realization of the long vowel 〈 -ä- 〉 . The results did not differ between the experimental groups that communicated with either the natural or the synthetic speech version of Mirabella. Testing the influence of the "Big Five" personality traits on the accommodating behavior revealed a tendency for neuroticism to influence the convergence of question intonation. On the level of individual speakers, we found considerable variation with respect to the degree and direction of accommodation. We conclude that phonetic accommodation on the level of local prosody and segmental pronunciation occurs in users of spoken dialog systems, which could be exploited in the context of computer-assisted language learning.